Health tourism and "smart specialisation" - Ognjen Blazevic (UTMS Journal of Economics, 2016)
The Europe 2020 strategy mapped out the direction for the achievement of smart, sustainable and inclusive growth and development. The purpose of the paper is confirmation of the hypothesis that health tourism, in all its complexity, interdiciplinarity and systematic approach to problems, is an ideal model of 'smart specialisation', not only of tourist regions, but the entire destination at the national level. National competitiveness in this paper can be improved by increasing innovation capacity by focusing on health tourism and health resources in general, through which also on the delivery of the objectives of the Europe 2020 strategy. The main research results are related to the fact that there is still no single definition of health tourism in theory and practice; however, using numerous serious research, the paper provides a general insight that health tourism can be viewed through the elements of the tourist offer which reflect the adequate combination of wellness and spa services with medical tourism services. The main conclusions in the paper are associated with some of the flagship initiatives in the document 'Europe 2020 - A European Strategy for Smart, Sustainable and Inclusive Growth' regarding health tourism, which, due to high correlation with smart, sustainable and inclusive development, proves to be a real developmental challenge and choice for reaching national and regional competitiveness.
Keywords: I150; O310; 330; wellness; spa; medical tourism; knowledge triangle; competitiveness; innovation